Development of transport system of the Republic of Kazakhstan - Semak, Y.A.; Raimbekov, B.Kh.; Assanova, M.K.; Kozhabergenova, A.Y. (Вестник Карагандинского университета, 2017)
The article discusses the state and development of the transport system of the Republic of Kazakhstan at the present stage. Development of the transport system is one of the most important conditions for the further re- structuring of the economy of the country and improving the competitiveness of the domestic goods and ser- vices in the world markets. The article considers the dynamics of the volume of transport services in recent years: passenger and freight transportation by pipelines. The article shows the importance of transcontinental routes passing through the vast territory of the Republic of Kazakhstan. The article considers the problems of development of the main modes of transport in Kazakhstan: rail and road. It shows a slight amount of wa- ter transport services are characterized by geographical features of the terrain and location. The measures to achieve the objectives of the use of the transport potential of the country are listed here . Particular atten- tion is paid to the key companies in the railway sector - JSC «National Company» ҚazaқstanTemіrZholy»». In the article attention is paid to the State program of development and integration of the transport system in- frastructure of Kazakhstan until 2020, provided the measures recommended therein. The transport complex of the Republic of Kazakhstan now provides the overall needs of the national economy and population in trans- port services. However, Kazakhstan has many ways of developing a transport potential.
Қазақстан Республикасы көлік жүйесінің дамуы
Развитие транспортной системы Республики Казахстан
Keywords: Transport systemt; cargo transportation; public transport; nland water transport; passenger traffic; cargo turnover; air transport; pipeline transportation